Terahertz applications of non-simply-connected and helical nanostructures - Collier, Thomas P. (Animo Repository, 2019)
We outline a range of proposals on using non-simply-connected and helical nanostructures for terahertz device implementations. We show that an Aharonov-Bohm quantum ring system and a double-gated quantum ring system both permit control over the polarization properties of the associated terahertz radiation. In addition, we review the superlattice properties of a nanohelix in external electric fields, which reveals negative differential conductance and photogalvanic effects. We present several schemes utilizing carbon nanotubes, including population inversion proposals for both quasi-metallic nanotubes (via generation of optically active hot electrons by an electric field), and metallic nanotubes (by optical excitation across a magnetic field-induced band gap). © Springer Nature B.V. 2019.